(untitled) (Physical Education, Health and Social Sciences, 2025)
Cerebral palsy (CP) is a non-progressive neurological disorder affecting motor function, often leading to spasticity and impaired hand motor function. This study aimed to compare the effectiveness of repetitive sensory stimulation (RSS) with a mesh glove alone versus RSS combined with a neurodevelopmental technique (NDT) in improving spasticity and hand motor function in hemiplegic CP patients. A randomized controlled trial (RCT) was conducted with 30 participants divided into two groups: Group A received RSS, while Group B received RSS combined with NDT. The study measured outcomes using the Modified Ashworth Scale and the Box and Block Test. Results indicated that both groups showed improvements, but the RSS + NDT group demonstrated significantly greater improvements in reducing spasticity and enhancing motor function. These findings suggest that integrating NDT with RSS is a more effective intervention for managing spasticity and improving hand motor function in hemiplegic CP patients.